Eksplorasi dan Identifikasi Bacillus sp. dari Tanah Rizosfer Bambu dan Tomat di Kelurahan Made, Sambikerep, Surabaya : Exploration and Identification of Bacillus sp. from Bamboo and Tomato Rhizosphere Soil in Made Village, Sambikerep, Surabaya - Fatimah Lailatus Saadah; Noni Rahmadhini; Suharto (Agrocentrum, 2023)
Bacillus sp. is one of the Biological Control Agents (BCA) that has effectiveness in inhibiting pathogenic bacterial and fungal pathogens. The purpose of this study was to determine the presence of Bacillus sp. on bamboo and tomato root soil. The research stage started from the exploration stage which was carried out on agricultural land in Made Village, Sambikerep District, Surabaya City. Soil sampling was taken compositely at 5 different points. From the isolation results, 6 bacterial colonies were found which were suspected to Bacillus sp. The six isolates were BS 1, BS 2, BS 3, BS 4, BS 5, and BS 6. Of the six colonies, only BS 3 colonies could not grow. The results of the isolation were then identified by colony morphology, physiological and biochemical characteristics. The results of the gram test showed that BS 2, BS 4, and BS 6 were gram-positive. The results of the soft rot test showed that BS 6 showed a positive reaction. So that it is suspected as Bacillus sp. are BS 2 and BS 4.